2019
DOI: 10.1186/s13046-018-1012-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Endoplasmic reticulum stress triggers Xanthoangelol-induced protective autophagy via activation of JNK/c-Jun Axis in hepatocellular carcinoma

Abstract: BackgroundXanthoangelol (XAG) was reported to exhibit antitumor properties in several cancer. However, the specific anti-tumor activity of XAG in human hepatocellular carcinoma (HCC) and the relevant mechanisms are not known.MethodsThe effects of XAG on HCC cell proliferation and apoptosis were respectively examined by CCK-8 assay and Annexin V-FITC/PI apoptosis kit. Western blotting was conducted to detect the expression of proteins. The effect of XAG on the development of acidic vesicle organelles was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…For example, autophagy induced by hispidulin has been found to alleviate sevoflurane‐induced neuronal apoptosis (Huang et al, ). A recent study also reported that autophagy‐mediated by ER stress abrogated the proapoptotic effect of Xanthoangelol in hepatocellular carcinoma (Li et al, ). Autophagy can not only block the induction of apoptosis by inhibiting the activation of apoptosis‐associated caspase but can also help to induce apoptosis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, autophagy induced by hispidulin has been found to alleviate sevoflurane‐induced neuronal apoptosis (Huang et al, ). A recent study also reported that autophagy‐mediated by ER stress abrogated the proapoptotic effect of Xanthoangelol in hepatocellular carcinoma (Li et al, ). Autophagy can not only block the induction of apoptosis by inhibiting the activation of apoptosis‐associated caspase but can also help to induce apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…Natural compounds and their derivatives have been shown to play an irreplaceable role in the discovery of new drugs with high‐efficiency and low‐toxicity (Ahmed and Ishibashi, ; Li et al, ). Several classes of compounds such as saponins, flavonoids, alkaloids, and polyphenols from natural products have been investigated for their anticancer activities (Han et al, ).…”
mentioning
confidence: 99%
“…The human GBM cell lines U373 and T98G were obtained from the Centre for Cell Resources of Shanghai Institutes for Life Sciences, Chinese Academy of Sciences (Shanghai, China). The cells were cultured and maintained in RPMI‐1640 medium with specific conditions, incubated in a humidified incubator at 37°C, 5% CO 2 (Li et al, ), and regularly operated by an inverted microscope. AIF (C20H16O5, purity: >99%) was obtained from Nu‐chek Prep (Elysian, MN).…”
Section: Methodsmentioning
confidence: 99%
“…The Editor in Chief retracted this article (1) because of significant concerns regarding a number of images presented in Figure 6c, which question the integrity of the data. It appears a number of the histopathology images have been published previously in unrelated articles (2,3,4). In additional, it appears that an image used in Figure 1c (SAOS-2 at 0uM) has also appeared in unrelated articles with different labels (5,6).…”
mentioning
confidence: 95%